Effects of Seed Invigoration Treatments on Seed Germination, Seedling Vigour and Physiobiochemical Characteristics of Angelica glauca EDGEW –An Endangered Medicinal Herb - Thakur, Anju; Sayal, Neha (International Journal of Bio-resource and Stress Management, 2018)
The present study was aimed to conserve Angelica glauca, a high altitude medicinal herb of North-Western Himalayas through innovative methodology to overcome dormancy, induction and synchronization of seed germination and vigour and also to understand underlying physio-biochemical changes. This species has become critically endangered on account of poor germination percentage, unsustainable and indiscriminate in-situ harvesting, so a prioritized herbal species for conservation. In nature Angelica glauca is generally propagated through seeds. Seeds of Angelica glauca show erratic, asynchronous and low germination due to embryonic immaturity and seed coat imposed dormancy which altogether decelerates the conservation strategy of this species. Seeds of Angelica glauca were collected from their natural populations at height of 1525 m amsl and tested for viability and germination. These seeds were further subjected to wide range of pre-sowing treatments. Study revealed that most of the tested treatments were found effective in improving germination and vigour as well as germination related indices. However, GA3 100 ppm for 72 hrs induced highest germination percentage (41.11%), followed by KNO3 500 ppm for 48 hrs (35.55%), PEG 6000 at -0.5 MPa for 12 hrs (33.33%) and thiourea 200 ppm for 30 mins (31.11%) as compared to control (22%). It was coupled with higher mobilization efficiency, imbibition capacity, α-amylase, protease and dehydrogenase activities , total soluble sugars and lower total phenols.